Aru Shah and the city of gold - Chokshi, Roshani (Chokshi, Roshani. Pandava novel, 2021)
"Aru Shah and her sisters--including one who also claims to be the Sleeper's daughter--must find their mentors Hanuman and Urvashi in Lanka, the city of gold, before war breaks out between the devas and asuras"--